A Preliminary Study on EFL Students’ Grammatical Competence in Descriptive Writing Task - Juliaty, Hanna; Abetnego, Demus (Universitas Sanata Dharma, 2019)
This study aims to identify and examine the ill-formed sentence construction in a descriptive text produced by Indonesian senior high school students, focusing on eight grammatical categories classified by James (1998): prepositions, articles, singular and plural nouns, adjectives, irregular verbs, tenses, concord and possessive case. The study used qualitative research and text analysis to examine five senior high school students’ descriptive texts. The findings showed that there were seven grammatical categories occurred in the ill-formed sentence construction in the students’ descriptive texts. Those grammatical categories include prepositions, articles, singular and plural nouns, adjectives, tenses, concord and possessive case. In addition, this study also found that the most frequently occurred ill-formed sentence construction in the descriptive text appeared in the grammatical forms of articles, tenses and concord.Keywords: descriptive text, English as a foreign language, grammar